Implementation of Participatory Leadership at Rabbani Elementary School, Bandung - Badrudin; Sinta Lestari; Silma Salsabila; Wiwin Rahmawati (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the implementation of participatory leadership in SD Rabbani Bandung and its impact on teacher work motivation and collaborative work environment. Participatory leadership, which involves teachers in decision-making, is expected to create a sense of belonging and improve their performance. This study uses a qualitative method with a descriptive approach. Data were obtained through in-depth interviews and documentation, with the principal as the main subject and teachers as supporting respondents. The results of the study indicate that the principal implements participatory leadership through the active involvement of teachers in the decision-making process, school program preparation, and performance evaluation. The principal also provides appreciation and discussion space that encourages teacher work motivation. The obstacles faced include resistance from new teachers and differences of opinion, which are overcome with an interpersonal approach and effective communication. These findings indicate that participatory leadership not only improves teacher motivation and performance but also creates an inclusive and productive work environment. This study contributes to the development of science in the field of education, especially in the application of leadership styles that support adaptive and highly competitive school management. These results are relevant to be implemented in various educational units to improve the quality of learning and collaboration in the school environment.